Asymmetric Information And Non-Performing Loans At Indonesian Bank - Pratesya, Ni Luh Gita; Gorda, Anak Agung Ngurah Oka Suryadinatha (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2025)
This study aims to analyze asymmetric information and non-performing loans in the Micro Community Business Credit program at Indonesian Bank. This study contributes to the understanding of how information imbalance, moral hazard, side streaming, credit appraisal, field monitoring, and managerial leadership interact in microcredit risk management. A descriptive qualitative approach was employed through in-depth interviews, observation, and documentation. The informants were selected purposively. The study also examined internal credit development data from July to December 2024. The findings show that non-performing loans are caused by internal bank limitations, customer-related factors, and external economic pressures. The study implies that strengthening post-disbursement monitoring, customer financial education, relational supervision, and adaptive leadership is essential to reduce credit risk.